2018
DOI: 10.1007/s00299-018-2281-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya

Abstract: Global gene expression analysis indicates host stress responses, mainly those mediated by SA, associated to the tolerance to sticky disease symptoms at pre-flowering stage in Carica papaya. Carica papaya plants develop the papaya sticky disease (PSD) as a result of the combined infection of papaya meleira virus (PMeV) and papaya meleira virus 2 (PMeV2), or PMeV complex. PSD symptoms appear only after C. papaya flowers. To understand the mechanisms involved in this phenomenon, the global gene expression pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 69 publications
1
12
0
1
Order By: Relevance
“…Other studies have also shown increased induction of SA signaling, defense response proteins or R-like genes in tolerant cultivars or in asymptomatic phases of infection compared to corresponding symptomatic interactions ( Sahu et al, 2012 ; Allie et al, 2014 ; Louis and Rey, 2015 ; Wang et al, 2016b ; Madronero et al, 2018 ). Many of these studies also noted altered primary metabolism.…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have also shown increased induction of SA signaling, defense response proteins or R-like genes in tolerant cultivars or in asymptomatic phases of infection compared to corresponding symptomatic interactions ( Sahu et al, 2012 ; Allie et al, 2014 ; Louis and Rey, 2015 ; Wang et al, 2016b ; Madronero et al, 2018 ). Many of these studies also noted altered primary metabolism.…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 95%
“…Transcriptome changes have been characterized at different stages of virus infection in a tolerant interaction ( Stare et al, 2015 ). Time-course studies have also allowed monitoring symptomatic and asymptomatic phases of infection associated with symptom recovery or with delayed symptom induction ( Allie et al, 2014 ; Madronero et al, 2018 ). Finally, transcriptomes or proteomes have been compared in susceptible, resistant or tolerant cultivars infected with the same virus strain ( Allie et al, 2014 ; Wang et al, 2016b ) or in plants infected with virulent or mild virus strains ( Kogovsek et al, 2016 ; Geng et al, 2017 ).…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 99%
“…In the case of light responses, pathogen infection reduces photosynthetic activity, as does PRSV, leading to a reprogramming of carbon metabolism and, therefore, to the expression of defense-related genes and chloroplast-derived ROS [51,52]. Infection with PapMV generates a transcriptomic profile similar to that produced by Papaya meleira virus (PMeV) infection in papaya plants, with expression of PR1, and ROS-related genes, but with lower expression of other defense-related genes, and no differential expression in the silencing machinery [53]. This would suggest that the antagonistic interaction could occur in combinations of PRSV with other viruses like PMeV, as these mixed infections occur in natural environments [15].…”
Section: Potyvirus Prsv Triggers Innate Immunity and Potexvirus Papmvmentioning
confidence: 99%
“…RNA-Seq has been used to find insights in several plant-virus interactions, including model plants such as Arabidopsis thaliana (Sun et al, 2016;Wu et al, 2016), plants of agronomical importance such as Oryza sativa (Blazquez et al, 2013;Wong et al, 2015), Zea mays (Chakrabarty et al, 2018), Manihot esculenta (Fang et al, 2014;Amuge et al, 2017;Anjanappa et al, 2018), Solanum tuberosum (Goyer et al, 2015;Stare et al, 2017) and tropical fruits such as C. papaya (Madroñero et al, 2018). However, to date (04-10-2019), a Google Scholar search, the NCBI PMC database, and the Web of Science using the queries "plant", "virus", "interaction", "transcriptome", "RNA-Seq", and "Colombia" with different combinations did not yield any results for plant-virus interactions research developed in Colombia.…”
Section: Ngs In Transcriptomics To Elucidate Plant-virus Interactionsmentioning
confidence: 99%